2016
DOI: 10.1111/ijcs.12320
|View full text |Cite
|
Sign up to set email alerts
|

Consumer decision‐making styles and post purchase behaviour of poor for Fast Moving Consumer Goods

Abstract: More than half of the world's population is poor. Certainly, their purchasing power cannot be compared with that of the riches, but it is their collective purchase potential which makes them a substantial market. The fast moving consumer goods (FMCGs), on the other hand, are the fourth largest industry in the world. FMCGs are relatively low cost products and the poor, by necessity, spend a significant amount of their income on FMCGs. So, by virtue of being a large consumer base for FMCGs, the poor are a promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…premium brands) with their budgetary constraints Costa Filho and Motta, 2015), this optimistic view should be taken with care. Other studies have shown that LICs are only moderately loyal or not loyal at all (Gbadamosi, 2009;Kumar et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…premium brands) with their budgetary constraints Costa Filho and Motta, 2015), this optimistic view should be taken with care. Other studies have shown that LICs are only moderately loyal or not loyal at all (Gbadamosi, 2009;Kumar et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Because of the dynamic characteristics of neurons and their connections with each other, this excitation mode will automatically change into a new equilibrium state. In this way, this kind of neural network can define the corresponding mode transformation and realize the mapping relationship [6].…”
Section: Basic Theory Of Artificial Neural Networkmentioning
confidence: 99%
“…The literature on consumer post-purchase behaviour has examined various factors associated with either repeat purchases or brand-switching behaviour, such as customer satisfaction, customer expectation, and consumer emotion (Kumar et al, 2017;Santos and Boote, 2003). Other studies on post-purchase behaviour have also evaluated the relationship between consumers' post-purchase and word-of-mouth (WOM) intention (Dellarocas and Narayan, 2006;Kuo et al, 2009).…”
Section: Consumer Post-purchase Behaviourmentioning
confidence: 99%
“…The literature on consumer post-purchase behaviour has examined various factors associated with either repeat purchases or brand-switching behaviour such as customer satisfaction, customer expectation and consumer emotion (Kumar et al , 2017; Santos and Boote, 2003). For example, Jones and Taylor (2018) investigate consumer responses to frontline employees’ requests for positive post-purchase evaluations, explaining the mixed feelings of consumers in response to employees’ requests in the post-purchase phase.…”
Section: Literature Reviewmentioning
confidence: 99%